History and Speculative Fiction - Hennessey, John L. (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
"Proposing a symbiosis between history and speculative fi ction, this wide-ranging collection of essays asks how critical visions of alternative possibility can help us confront the dire legacies of colonialism, the specter of ecological catastrophe, and the burdens of systemic injustice. Historians and literary scholars alike should welcome this intervention." -John Rieder, Professor Emeritus, University of Hawai'i, Mānoa "This volume makes a substantial contribution to the scholarship on speculative fi ction by illuminating how the concept of 'concurrences,' as articulated and theorized by Gunlög Fur, can serve as a valuable methodological tool in the study of speculative fi ction. Drawing on a wide variety of cultural and historical sources, the essays in this volume offer useful case studies that render the concept of concurrences more comprehensible through concrete application." -Cyrus R. K. Patell, New York University This open access book demonstrates that despite different epistemological starting points, history and speculative fiction perform similar work in "making the strange familiar" and "making the familiar strange" by taking their readers on journeys through space and time. Excellent history, like excellent speculative fiction, should cause readers to reconsider crucial aspects of their society that they normally overlook or lead them to reflect on radically different forms of social organization. Drawing on Gunlög Fur's postcolonial concept of concurrences, and with contributions that explore diverse examples of speculative fiction and historical encounters using a variety of disciplinary approaches, this volume provides new perspectives on colonialism, ecological destruction, the nature of humanity, and how to envision a better future. John L. Hennessey is a research fellow in the History of Ideas and Sciences at Lund University. He has published on global colonial history and the history of science in journals including Science in Context, History and Anthropology, French Colonial History, Settler Colonial Studies and Japan Review. .